Shortcuts in particle production in a toroidally compactified space-time - Da Silva, J. M. Hoff [UNESP]; Da Rocha, R. (World Scientific Publishing, 2007)
We investigate the particle production in a toroidally compactified space-time due to the expansion of a Friedmann cosmological model in ℝ3 × S1 outside a U(1) local cosmic string. The case of a Friedmann space-time is also investigated where torsion is incorporated in the connection. We present a generalization to toroidal compactification of p extra dimensions, where the topology is given by ℝ3 × Tp. Some implications are presented and discussed. Besides the dynamics of space-time, we investigate in detail the physical consequences of the topological transformations. © World Scientific Publishing Company.
Keywords: Compactification; Cosmic string; Extra-dimension; Particle production; Torsion